Text Mining Analysis untuk Identifikasi Artikel Hoax Menggunakan Algoritma Cosine Similarity - Yulianty Lasena; Husdi Husdi; Maryam Hasan (KITA Institute, 2020)
The impact of significant technological developments in everyday life starts from simple activities to activities that require a high level of precision. The development of information technology also contributes to the dissemination of news. In Indonesia, Information Technology is also developing rapidly where internet users currently number 132.7 million or 52% of Indonesia's population. The exchange of information between people is a positive thing, but its dissemination through social media is not all facts. In a number of cases that have occurred, for example the spread of news that is not factual is often called a hoax. The latest technology that can help overcome this, one of which is the technology known as Text Mining. This is used to solve problems faced by internet users with fake information (hoax).